Examining the Determinants of Food Prices in Developing Asia - Hyeon-seung Huh; Cyn-Young Park (Asian Development Bank (ADB), 2013)
How the price of food is determined has become a critical issue, given the drastic surges in prices in recent years and the prevailing expectation of further increases. Along this line, this paper examines the sources of food price fluctuations in 11 developing Asian countries. The working model is a block vector autoregression (VAR), and 10 variables are classified into three blocks - world, region, and country - depending on their origin and nature. Empirical evidence shows that the regional shock plays a pivotal role in explaining the variations of domestic food prices, particularly at medium- to long-term horizons. Contrary to conventional belief, the world food price shock contributes little to the dynamics of domestic food prices in developing Asia. The findings suggest Asian food markets are more integrated regionally than with the world market. The short-run movements of domestic food prices are accounted for largely by the country's own shock. Taken together, our findings suggest that promoting food price stability would require efforts at the regional level as well as at the domestic level, reflecting the influence of region-specific factors. Extensions to the developing countries in other regions produce similar findings on the determination of food prices.
hdl:11540/2076
Keywords: C32; F15; Q11; 330; food price; developing Asia; Shocks; block VAR